Transactional sex and the challenges to safer sexual behaviors: a study among male sex workers in Chennai, India. - Biello, Katie B; Thomas, Beena E; Johnson, Blake E; Closson, Elizabeth F; Navakodi, Pandiaraja; Dhanalakshmi, A; Menon, Sunil; Mayer, Kenneth H; Safren, Steven A; Mimiaga, Matthew J (AIDS care, 2016)
Male sex workers (MSW) are a significant but invisible population in India who are at risk for HIV/sexually transmitted infections (STIs). Few studies from India have documented HIV risk factors and motivations for sex work in this population. Between 2013 and 2014, a community-based convenience sample of 100 MSW in Chennai (south India) completed a baseline risk assessment as part of a behavioral intervention. Participants were ≥18 years, and reported current sex work. We report medians and proportions, and Wilcoxon-Mann-Whitney and chi-square tests are used to examine differences between sex work and sexual behavior measures by income source. Participants were engaged in sex work for 5.0 years (IQR = 2.3-10.0), and earned 3000 (IQR = 2000-8000) Rupees (<50 USD) per month from sex work. Sixty-four percent reported ever testing for HIV and 20.2% for any STI. The most common reasons for starting sex work were money (83.0%) and pleasure (56.0%). Compared to participants with an additional source of income, those whose only source of income was sex work reported more male clients in the past month (10.0 vs. 6.0, p = .017), as well as more condomless anal sex acts with male clients (8.0 vs. 5.0, p = .008). Nearly 70.0% were offered more money not to use a condom during sex with a client, and 74.2% reported accepting more money not to use a condom. Three-quarters reported having experienced difficulty using condoms with clients. MSW in India engage in high levels of sexual risk for HIV/STIs. Money appears to be a driving factor for engaging in sex work and condomless sex with clients. HIV prevention interventions with MSW should focus on facilitating skills that will support their ability to negotiate sexual safety in the context of monetary disincentives.